A microscopic gas-solid drag model considering the effect of interface between dilute and dense phases. (July 2020) - Chen, Xiao; Song, Nan; Jiang, Ming; Ma, Teng; Zhou, Qiang
Highlights: Significant drag deviation is found at the gas-structure interface at microscales. Concentration gradient and superficial velocity gradient are important markers. A microscopic drag model considering the interface effect is established via PR-DNS. Abstract: Particle-resolved direct numerical simulations (PR-DNSs) are employed to simulate flows past various stationary clusters of spheres in low-particle-Reynolds-number regime. The results show that the drag force at the interface between the dilute and dense phases is significantly different from the prediction of the traditional homogeneous BVK law (AIChE Journal, 2007, 53(2):489-501). The drag force at the interface is found to be the function of the solid volume fraction gradient, the superficial velocity gradient and the size of the grid on which the drag force is computed. Based on the PR-DNS data, a new microscopic drag model considering the interface effect is formulated. The effectiveness of the new drag models is demonstrated in flows past ellipsoidal clusters of particles. The results show that, in terms of the global drag force on the clusters, the difference between the prediction of the new model and the PR-DNS data is generally less than 17%. While the prediction of the BVK law is more than 200% larger than the PR-DNS data. The comparison is made at the grid size of three times of the particle diameter, which is a commonly adopted size in fine-grid two fluid model as well as computational fluid dynamics-discrete element method simulations. Therefore, the new drag model is very promising in resolving the detailed interactions between the gas and solid phases in flows with complex fine structures such as riser flows.